Macrophage activity in resistant and susceptible mouse strains infected with Mycobacterium lepraemurium. - Brett, S J (1988)
The level of activation of peritoneal macrophages following subcutaneous inoculation of resistant (C57BL) and susceptible (BALB/c) mice was assessed by monitoring superoxide anion and hydrogen peroxide production and also tumour cell cytostasis. The level of systemic macrophage activation appeared to correlate with bacterial load, rather than resistance to infection. It was observed that the more susceptible (BALB/c) strain developed higher and more sustained levels of systemic macrophage activation, whereas the more resistant (C57BL) strain showed only low transient levels of macrophage activation. In contrast, in vivo challenge of subcutaneously infected C57BL mice, via the intra-peritoneal route, with heat-killed Mycobacterium lepraemurium and thioglycollate resulted in a high level of macrophage activation compared with similarly treated uninfected mice. Similar treatment of susceptible BALB/c mice, however, did not result in enhanced macrophage activation. It was also observed that high levels of macrophage activation occurred in T-cell deprived C57BL mice following infection with M. lepraemurium.